Echocardiographic evaluation of crab-eating foxes (Cerdocyon thous) in captivity - Ana Flávia D.P. Arruda; Liliane R. Nascimento; Suzana A. Tsuruta; Vanessa M.F. Milken; André Luis Q. Santos; Maressa B. Silva; Luiza G. Dias; Matheus M. Mantovani (Pesquisa Veterinária Brasileira)
ABSTRACT: The cardiac evaluation of wild animals is still a wide and largely unknown field for several species. Thus, the objectives of this study were to evaluate cardiac function through echocardiography and obtain echocardiographic values for crab-eating foxes under pharmacological restraint. This study was done with eight males and two females under pharmacological containment of intramuscular acepromazine with meperidine followed by intravenous propofol. In the two-dimensional mode, the diameter of the aorta and left atrium and the LA/Ao ratio were obtained. In M-mode, the internal diameter of the left ventricle was measured during diastole and systole, and the shortening fraction was calculated. In the transmitral flow using the pulsed Doppler mode, we analyzed the E-wave velocity peak, A-wave velocity peak, and E/A ratio. The analysis of the isovolumetric relaxation time was performed in the apical view of five chambers using an intermediate flow between mitral influx and aortic flow, and the E-wave deceleration time was calculated. The measurements of position and dispersion of all variables were calculated, and the respective confidence intervals were set at 95%. The Doppler echocardiographic values are closer to domestic dogs, the left ventricle internal diameter in diastole was lower, and the ejection fraction was closer to that of maned wolf (Chrysocyon brachyurus). Cardiology parameters found in this study can be used as specific values for this species in the evaluation of cardiac function, as well as in other additional studies in wild animal cardiology.